Entrepreneurship Intention among Nepalese MBA Graduates: Impact of Entrepreneurial Ecosystem Factors (International Journal of Social Research & Innovation, 2023)
The purpose of the research presented in this paper is to examine the effects of seven entrepreneurial ecosystem factors on entrepreneurship intention among Nepalese MBA students, in Kathmandu Valley. The research employed structural equation modelling (SEM) to interpret the perception-based survey data collected from 343 respondents. The empirical results indicate a strong positive correlation between individual capabilities and entrepreneurial intention. Students’ perception of an informal support system has a significant positive effect on entrepreneurial intention. The study suggested that an elevated level of entrepreneurial ecosystem development is not required to influence entrepreneurial intention; improvement on some factors like family and social support, skill-building education, and training might increase entrepreneurial intentions. This research offers educators and policymakers with the opportunity to develop entrepreneurial skills among students, and to provide the infrastructure support which can serve as a basis for translating intentions into actions to address significant employment gaps present in developing economies like Nepal.